To study the relationship between work-life balance initiatives and employees behavioral outcomes: moderator emotional intellifence among employees in banking industry - Ericia, Lee Kai Xin (Universiti Malaysia Sarawak (UNIMAS), 2019)
The purpose of the research to study the relationship between work life balance initiatives and employee's behavioral outcomes with the moderate effect of emotional intelligence among employees in banking industry. The work life balance initiatives in this research indicated dependent care initiatives, flexible work arrangement and work leave programme and employee's behavioral outcomes with job satisfaction. This research using cross-sectional and quantitative research design with sample size 90 respondents from selected bank in Sarawak. Questionnaire with five Likert scale are distributed to each employees to study the according topic. The data are gather and analysed using SPSS and Jamovi which the method using are Pearson correlation to study the relationship between work life balance initiatives and employee's behavioral outcomes with the moderate effect of emotional intelligence. The result come out also being sustain by past research and theory like spill over theory. A suitable work life balance initiatives will increase employee's behavioral outcomes. Emotional intelligence have a weak moderate effect on employee's behavioral outcomes while develop work life balance initiatives.